Therapeutic strategy and prognostic analysis of inflammatory myofibroblastic tumor in the head and neck: a retrospective study - Feng Liu; Yanchao Qin; Zhiwei Zhang; Mengru Li; Bowei Feng; Wei Ding; Shubin Dong (PeerJ)
Objective This study aimed to investigate the clinical features, treatment methods, and prognosis of head and neck inflammatory myofibroblastic tumor (HNIMT). Methods A retrospective analysis was conducted using the clinical data of 12 HNIMT patients who were admitted to Shanxi Cancer Hospital between January 2016 and December 2023. This analysis focused on their clinical manifestations, pathological characteristics, treatment strategies, and prognosis. Results Among the 12 cases analyzed, four involved inflammatory myofibroblastic tumors (IMT) located in the nasal sinuses or nasopharynx, with symptoms including nasal congestion, rhinorrhea, and maxillofacial swelling. Two cases each in the salivary glands and oral cavity presented as localized, painless masses. One right cervical IMT case also presented as a painless lump. Two laryngeal IMT cases had hoarseness, and one subglottic endotracheal IMT case showed inspiratory dyspnea. All patients received surgery, with postoperative pathology confirming IMT. During follow-up, four cases recurred. Finally, nine patients were disease-free, two survived with disease, and one died. Conclusions HNIMT is a rare, low-grade malignant or borderline tumor that is generally associated with a favorable prognosis. Accurate diagnosis relies on pathological examination, and surgical resection remains the primary treatment for HNIMT. The need for adjuvant therapy following surgery should be determined by clinicians based on tumor location, surgical approach, and the presence of high-risk factors.